The Effectiveness of Duolingo in Improving Students’ Speaking Skill at Madrasah Aliyah Bilingual Batu School Year 2019/2020 - Hafifah Hafifah (Language-Edu, 2021)
Duolingo is a great example of straightforward language application. Duolingo can help someone to develop his or her speaking skill in communication. By using Duolingo application as an efficient media to develop the speaking skills of students. The purpose of this study is to proof the effectiveness of using Duolingo in improving students’ speaking skills.This study is a kind of quasi-experimental which the population of this study was the tenth grade of Madrasah Aliyah Bilingual Batu. The samples are consist of 20 students from X IPS 2 as the experimental group and 20 students from X IPS 1 as the control group. The experimental group got the treatment by using the Duolingo application and the control group taught with conventional technique or textbook-based. The research instruments were the Questions and Answers test and rubric of speaking. The data of the resarch were analyzed by using a t-test. Based on the statistical calculation with the significance level of 0.05 (5%), it presented that t0= 2.881 is higher than tt = 1.672. The result of this study shows that the use of Duolingo is significant to improve students’ speaking skills at tenth-grade students in MA Bilingual Batu school year 2019/2020.